First occurrence of the black field earwig, Nala lividipes (Dermaptera: Labiduridae) in Greece - Koutsoukos, Evangelos; Demetriou, Jakovos; Kalaentzis, Konstantinos; Kazilas, Christos (ENTOMOLOGIA HELLENICA, 2022)
The cosmopolitan black field earwig, Nala lividipes (Dufour, 1820) (Dermaptera: Labiduridae) is observed for the first time in Greece. A photographic record was obtained by the first author in 2016, from Salamis Island followed by a photographic citizen-science observation from Rhodes in 2021. Despite frequent inspections and efforts to raise public awareness, no additional samples or observations have been recovered. The poor study of Dermaptera in Greece and the absence of early warning systems for alien insects, may have delayed the detection of this alien species in the country. However, given the agricultural significance of N. lividipes, a short description is given to assist further data collection and monitoring. Finally, the potential establishment of the earwig in Greece, along with the impacts on the native flora and fauna are discussed.